Impact of Hearing Loss on Geriatric Assessment - Völter, Christiane (Clin Interv Aging, 2020)
BACKGROUND: Due to the aging society, the incidence of age-related hearing loss (ARHL) is strongly increasing. Hearing loss has a high impact on various aspects of life and may lead to social isolation, depression, loss of gain control, frailty and even mental decline. Comorbidity of cognitive and sensory impairment is not rare. This might have an impact on diagnostics and treatment in the geriatric setting. OBJECTIVE: The aim of the study was to evaluate the impact of hearing impairment on geriatric assessment and cognitive testing routinely done in geriatrics. MATERIAL AND METHODS: This review is based on publications retrieved by a selective search in Medline, including individual studies, meta-analyses, guidelines, Cochrane reviews, and other reviews from 1960 until August 2020. RESULTS: Awareness of sensory impairment is low among patients and health professionals working with elderly people. The evaluation of the hearing status is not always part of the geriatric assessment and not yet routinely done in psychiatric settings. However, neurocognitive testing as an important part can be strongly influenced by auditory deprivation. Misunderstanding of verbal instructions, cognitive changes, and delayed central processes may lead to a false diagnosis in up to 16% of subjects with hearing loss. To minimize this bias, several neurocognitive assessments were transformed into non-auditory versions recently, eg the most commonly used Hearing-Impaired Montreal Cognitive Assessment (HI-MoCA). However, most of them still lack normative data for elderly people with hearing loss. CONCLUSION: Hearing loss should be taken into consideration when performing geriatric assessment and cognitive testing in elderly subjects. Test batteries suitable for ARLH should be applied.